Ferri- and ferro-electric switching in spontaneously chiral polar liquid crystals - Jordan Hobbs; Calum J. Gibb; Richard. J. Mandle (Nature Communications)
Abstract The recent discovery of spontaneous chiral symmetry breaking has demonstrated the possibility of discovering the exotic textures of ferromagnetic systems in liquid crystalline fluid ferro-electrics. We show that the polar smectic mesophase exhibited by the first molecule discovered to exhibit a spontaneously chiral ferroelectric nematic phase is also helical has a strongly varied textural morphology depending in its thermal history and phase ordering. Electro-optic studies demonstrate that the two spontaneously chiral phases exhibit field-induced phase transitions. For the nematic variant, this process is threshold-less and has no hysteresis, while for the smectic it has a clear threshold and shows hysteresis meaning this phase exhibits pseudo-ferrielectric switching, the first of its kind for ferroelectric nematic like phases. We show that helix formation can be both 1st and 2nd order, but when it is 1st it is accompanied by pre-transitional helix formation extending from the phase boundary into the preceding ferroelectric nematic phase.